PENGARUH MEDIA PROMOSI DIGITAL ATAU ONLINE DAN VIRAL MARKETING TERHADAP KEPITUSAN PEMBELIAN PADA BELANJADOLO ONLINE SHOP DI KECAMATAN BANJARNEGARA - Lustono Lustono (Medikonis, 2020)
ABSTRCT This study analyzes the effect of Digital or online promotional media and viral marketing on purchasing decisions in belanjadolo online shop in Banjarnegara District. The sample used in this study is consumers belanjadolo online shop in Banjarnegara District.This type of research used in this research is associative using quantitative descriptive methods. The data used in this study are primary data. The population in this study is belanjadolo online shop consumers in the Banjarnegara District. The sampling technique in this study uses the slovin formula. Obtained a sample of 82 consumers. Data analysis in this study used multiple linear regression analysis with SPSS software. The results showed that the variable digital or online promotional media had a positive and significant effect on purchasing decisions. Viral marketing has no significant effect on purchasing decisions. Variable Digital or online promotional media and viral marketing together influence on purchasing decisions. This study has limitations, namely the period in this study is relatively short, only 8 months. The influence of the independent variables on the dependent variable in this study amounted to 53.6%. Suggestions for further research is to add a period of research time.